Back Cover: A Catalytic Microwave Process for Superfast Preparation of High‐Quality Reduced Graphene Oxide (Angew. Chem. Int. Ed. 49/2017). Issue 49 (7th November 2017) - Liu, Runze; Zhang, Yu; Ning, Zhenjian; Xu, Yuxi
Abstract : The microwave exfoliation and reduction of graphite oxide (GO) in ambient air are greatly promoted by a small amount of graphite, which unexpectedly acts as a catalyst. In their Communication onpage 15677 ff., Y. Xu and co‐workers show that the catalytic microwave exfoliated graphite oxide (CMEGO) product displays ultrahigh electrochemical performances as anodes for both lithium‐ion and sodium‐ion batteries.